Modified Huanjingjian Prevents Chemotherapy-Induced Alopecia by Inhibiting Genomic DNA Methylation of the Wnt Signaling Pathway in Mice - Liu X; Du T; Xi R; Cheng L; Wang Y; Lu H; Guo D; Zhu J; Liu T; Li F (Drug Design, Development and Therapy)
Xin Liu,1,* Ting Du,1,* Ruofan Xi,1,* Linyan Cheng,1 Yi Wang,1 Hanzhi Lu,1 Dongjie Guo,1 Jianyong Zhu,2 Te Liu,3 Fulun Li1 1Department of Dermatology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200437, People’s Republic of China; 2Department of Pharmacy Research, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200437, People’s Republic of China; 3Shanghai Geriatric Institute of Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200031, People’s Republic of China*These authors contributed equally to this workCorrespondence: Te Liu, Shanghai Geriatric Institute of Chinese Medicine, Shanghai University of Traditional Chinese Medicine, 365 South Xiangyang Road, Shanghai, 200031, People’s Republic of China, Email liute1979@shutcm.edu.cn Fulun Li, Department of Dermatology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, 110 Ganhe Road, Shanghai, 200437, People’s Republic of China, Email drlifulun@163.comAim: Cyclophosphamide (CTX), a cornerstone in breast cancer combination chemotherapy, frequently induces adverse effects including myelosuppression, gastrointestinal disturbances, hepatic impairment, and alopecia. Chemotherapy-induced alopecia severely impacts patients’ quality of life and psychological well-being. Modified Huanjingjian (MHJJ), a traditional Chinese herbal formula, demonstrates clinical efficacy in alleviating chemotherapy-related side effects, yet its mechanisms against CTX-induced alopecia remain uncharacterized. And our main aim was to explore the efficacy and the mechanism of MHJJ in mice.Methods: UPLC-QE-Orbitrap-MS characterized MHJJ’s chemical composition. A CTX-induced alopecia murine model was established. Systemic toxicity was evaluated through body weight monitoring, automated biochemical analysis (ALT/AST levels), and hematological profiling (WBC/PLT counts). Hair follicle histopathology was assessed via H&E staining. IHC and IF staining quantified proliferation markers and hair follicle stem cell (HFSC) biomarkers. Reduced representation bisulfite sequencing (RRBS) was used to map DNA methylation patterns. Wnt pathway dynamics were analyzed through qRT-PCR and IF staining.Results: We identified 110 bioactive compounds in MHJJ. MHJJ intervention attenuated alopecia severity, restored follicular architecture, and increased follicular density compared to CTX monotherapy (p< 0.05). HFSC proliferation markers (Ki67/CD34) showed significant upregulation, while apoptosis markers (Caspase-3) were suppressed. RRBS revealed MHJJ-mediated hypomethylation in differentially methylated regions, with gene body methylation constituting 60% of total methylation changes. Methylation-modulated genes predominantly localized to Wnt signaling pathways: MHJJ enhanced Wnt3/Wnt10a expression while suppressing Cer1/Axin1. Corresponding methylation reductions at promoter and gene body regions were confirmed at mRNA and protein levels.Conclusion: MHJJ mitigates CTX-induced alopecia through epigenetic regulation of HFSCs, specifically via DNA hypomethylation-mediated activation of Wnt3/Wnt10a and suppression of Cer1/Axin1. This mechanism promotes follicular regeneration by restoring Wnt signaling homeostasis, positioning MHJJ as a promising adjuvant for chemotherapy-induced alopecia management. Keywords: traditional Chinese medicine, chemotherapy-induced alopecia, hair follicle, DNA methylation, Wnt signaling pathway